Favorable response to PD-1 inhibitor plus chemotherapy as first-line treatment for metastatic follicular dendritic cell sarcoma of the spleen: a case report - Li, Jielang; Ren, Min; Bi, Feng; Chen, Ye; Li, Zhiping (Frontiers in Immunology, 2023)
Follicular dendritic cell sarcoma (FDCS) is an uncommon low-grade malignant sarcoma. For localized FDCS, surgery is the most commonly recommended therapy option. However, there is no standard treatment protocol for metastatic FDCS. Here, we present a 68-year-old female with primary spleen FDCS who had multiple peritoneal metastases. She was treated with sintilimab (PD-1 inhibitor) plus chemotherapy (epirubicin plus ifosfamide) as first-line treatment achieving partial response (PR) and a relatively long progression-free survival (PFS) of 17 months. This case suggests that PD-1 inhibitor plus chemotherapy as first-line therapy seem to be a promising treatment option for metastatic FDCS.